Neutron diffraction of deuterated tripalmitin and the influence of shear on its crystallisation. (July 2019) - Stuart, B.H.; Maynard-Casely, H.E.; Booth, N.; Leung, A.E.; Thomas, P.S.
Highlights: Polymorphic structures adopted by deuterated tripalmitin on cooling have been characterised using neutron diffraction. For shear studies, simultaneous rheological data from a Couette cell was collected with neutron diffraction data. Tripalmitin was observed to directly transform from a liquid phase to a β polymorph under the influence of shear. Temperature at which β transition occurs is independent of shear rate, but shear forces influence crystalline order. Abstract: This neutron diffraction study of deuterated tripalmitin has provided further insight into a forensic observation of the crystallisation of lipids under high-shear conditions. To achieve this, an experimental set up was designed to enable simultaneous rheological data from a Couette cell to be recorded with neutron powder diffraction, enabling the influence of shear on the polymorph transformation on cooling to be monitored in real time. Tripalmitin was observed to directly transform from a liquid phase to a β polymorph under the influence of shear. Although the liquid to β transition was not observed to be influenced by shear rate, the degree of crystallinity, qualitatively denoted by an increase in the sharpness of the diffraction peaks, was observed at higher shear rates. Evidence is also presented that the rate of cooling influences the ordering in the β-polymorph produced in zero shear conditions.